Genetic Analysis for Panicle Architecture and Grain Yield in Sorghum [Sorghum bicolor (L.) Moench] in Mali - Sako, D. (University of Ghana, 2013)
Sorghum panicle architecture is a complex trait involving growth, elongation and branching pattern. The main objective of this research was to determine the genetic control of sorghum panicle architecture and its involvement in grain yield. Molecular markers associated with statistical analyses were used to identify the genomic regions or QTLs controlling quantitative traits. A population composed of 401 F 4 families was derived from a cross between two contrasted parents for panicle traits (Tiandougou and Lata-3). Phenotyping of sorghum panicle architecture was based on two groups of variables: architectural geometry traits related to the length and the diameter and architectural topology traits that relate to the number, density and position. Forty eight sorghum panicle architecture traits and grain yield components were studied in three sowing dates in two years at the research station of Sotuba, Bamako, Mali. A linkage map was constructed using 228 SNP. A total length of the genetic map was 1362.3 cM with average distance between markers of 6.01 cM. In this study, 164 QTLs including 53 major QTLs were detected for the different traits. These putative QTL explained 1.91 to 45.64% of the phenotypic variation observed for each trait. Many of the major QTLs were consistent across the sowing dates. Key regions of the genome in the population Tiandougou/Lata-3 affecting panicle growth, elongation and branching may be utilized to improve agronomic performance through MARS approach. Sorghum grain yield was positively influenced by the following panicle architecture traits: primary branches number and length, rachis basal diameter and the number of nodes per panicle. These traits can be used for indirect selection for yield potential improvement in conventional or molecular breeding methods. QTLs and candidate genes involved in inflorescence architecture in related grasses were co- localized. These associations may be investigated in sorghum to decipher the function and pattern of these candidate genes.
Thesis (PhD) - University of Ghana, 2013